THE ROLE OF MODERN LECTURES IN THE EDUCATION SYSTEM - Masuda Irgasheva (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
In the article, it was considered that the transmission of data and information in the form of lectures is one of the teaching methods in the higher education system and is a process that depends on the level of knowledge, qualifications, basic information and age of the students, and in some cases, gender.